(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
The research work was aimed at investigating physiological, biochemical, analgesic and anesthetic indices of dogs anesthetized with propofol-ketamine and maintained with repeat bolus and constant infusions of propofol. Eight dogs, assigned to two groups (n=4), were used in this study. All dogs were pre-medicated with atropine (at 0.03 mg/kg bwt) and xylazine (at 2 mg/kg bwt). Anesthesia was induced by a concurrent administration of propofol (at 4 mg/kg bwt) and ketamine (at 2.5 mg/kg bwt). Maintenance of anesthesia in Group 1 was done with a repeat bolus of propofol (at 2 mg/kg bwt), while in Group 2 it was done with a constant infusion of propofol (at 0.2 mg/kg bwt/min). Gastrotomy was performed in both groups, and anesthesia was maintained for 60 min. Physiological, analgesic, anesthetic parameters and plasma glucose concentration were measured. There was no significant (P>0.05) difference found in the analgesia and pedal reflex scores, durations of analgesia and recumbency, recovery time and standing time between the groups. The heart rate, respiratory rate and rectal temperature reduced significantly (P<0.05) from the baseline values. The heart and respiratory rates were significantly (P<0.05) lowered in Group 1 than in Group 2. Blood glucose was significantly (P<0.05) elevated at recovery from anesthesia in both groups. However, the value did not differ significantly (P>0.05) between the groups. In conclusion, both maintenance protocols are suitable for dogs, although the repeat bolus technique produces marked cardiopulmonary depression. http://dx.doi.org/10.5455/javar.2015.b114